Analisis Struktur Kinerja Kluster Industri Unggulan Di Kabupaten Sidoarjo - Ery Chusnul Aldi; Safira Aprilia Lukita; Muhammad Yasin (Journal of Creative Student Research, 2023)
This study discusses the analysis of the power structure of leading industry clusters in Sidoarjo Regency. Sidoarjo Regency is one of the districts in East Java Province that has the potential and success in developing the local economy through the formation of industrial clusters. This study uses descriptive qualitative research methods by collecting secondary data through literature analysis. The results of the analysis show that factors such as superior natural resources, infrastructure availability, labor skills, research and innovation facilities, and government support policies affect the successful formation of leading industrial clusters in Sidoarjo Regency. Industrial clusters increase productivity, efficiency, innovation and commercialization. This study provides an understanding of the characteristics and dynamics of leading industry clusters in Sidoarjo Regency and the factors that influence efficiency. The results of this study can be the basis for further development to optimize the economic potential of the region with the help of industrial clusters.